2012
DOI: 10.1016/s1995-7645(11)60242-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative pharmacological and phytochemical analysis of in vivo & in vitro propagated Crotalaria species

Abstract: These findings indicate compounds isolated from ethanolic extracts of Crotalaria sps., possesses pharmacological properties and potential to develop natural compounds based pharmaceutical products. The IC(50) values for ethanolic extracts of Crotalaria sps. was evaluated through the Linear regression analysis (R(2) ≤ 1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 13 publications
0
12
0
3
Order By: Relevance
“…We found that all Crotalaria species in the Karen villages we studied were used for medicinal purposes, which was different from their popular uses at a global level. Because Crotalaria species contain useful secondary compounds, such as alkaloids, saponins, and flavonoids, they can be used as medicine [28]. Flemingia and Senna are commonly found in the villages, making them easy to obtain and use by villagers [29], and both genera are much used in traditional medicine.…”
Section: Traditionally Used Leguminosaementioning
confidence: 99%
“…We found that all Crotalaria species in the Karen villages we studied were used for medicinal purposes, which was different from their popular uses at a global level. Because Crotalaria species contain useful secondary compounds, such as alkaloids, saponins, and flavonoids, they can be used as medicine [28]. Flemingia and Senna are commonly found in the villages, making them easy to obtain and use by villagers [29], and both genera are much used in traditional medicine.…”
Section: Traditionally Used Leguminosaementioning
confidence: 99%
“…The most important bioactive compounds of the medicinal plants are alkaloids, flavanoids and phenolic compounds [11]. Natural antioxidants mainly come from plants are in the form of phenolic compounds such as flavonoids, phenolic acids, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Recent findings about species of the genus Crotalaria describe their biological activity, by example the ethanolic fractions of C. retusa, the chloroform fraction of C. prostrate, the ethanolic extract of C. medicaginea, the ethanolic extract of C. pallida, the methanolic extract of C. burhia, and the fractions of C. bernieri and C. madurensis showed inhibitory capacity against E. coli [4,9,10,13,21]. The species C. longirostrata has been reported to have ethnobotanical activity, but an antimicrobial evaluation had not yet been done, and the chemical compounds responsible remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the use of natural products for the management of fungal diseases in plants is considered a reasonable substitute for synthetic fungicides [3]. The genus Crotalaria includes around 600 species distributed throughout the tropics and subtropical regions of the world, which have been used as antagonists to nematodes in sustainable crop production systems [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation